Pengaruh Pola Asuh dan Lingkungan Masyarakat Terhadap Hasil Belajar IPA Siswa Kelas V SDI Harekakae, Kabupaten Malaka - Maria Yovita Bano; Yohana Febriana Tabun; Damian Puling; Yanuarius Bria Seran (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This research aims to find out how much influence parenting patterns and the influence of the community environment have on the science learning outcomes of class V students at SDI Harekake, Malacca Regency. Data in the research were taken using questionnaires and tests. The questionnaire was divided into two groups, namely to reveal data on parenting patterns and the community environment. Test scores are used to reveal the science learning outcomes of fifth grade students at SDI Harekakae. The analysis technique used in hypothesis testing is a multiple linear analysis technique. The results of the research show that, there is no significant influence between parenting styles on the science learning outcomes of class V students at SDI Harekakae with a significance value of 0.1630 > 0.05. There is no significant influence between the community environment on the science learning outcomes of fifth grade students at SDI Harekakae. This is proven by the calculation results which show a significance value of 0.0826 > 0.05 and there is no significant influence between parenting style and the community environment on science learning outcomes. fifth grade student at SDI Harekakae. Because the significant value of parenting patterns and the community environment is greater than the Alpa Value.